Anatomy of the Mechanism or Self-Regulation in the Russian Style - Logvinov, Victor (project baikal, 2016)
The article describes the situation in the contemporary Russian architecture, where the state control over business is legislatively called off, the public consumer control has not yet matured, the professional control is beyond the law, and such notions as ‘professional honour’, ‘conscience’, ‘reputation’ and ‘public opinion’ lose their value.